Educazione e pacifismo nelle lettere tra Ellen Key e Romain Rolland - Pironi, Tiziana (Studi sulla Formazione/Open Journal of Education, 2016)
Starting point of this article is the unpublished correspondence between the Swedish pedagogue Ellen Key (1849-1926) and the French writer Romain Rolland (1866-1944) that took place in the years between 1911 and 1926. The exchange of letters between the two figures is a significant document in the history of European culture during the First World War, from which it is possible to extrapolate an educational message, which aims to lay the basis to the education of the European citizen of the future..